Aspects of staffing and human resources potential in the security-oriented management of business processes during the restoration of national economic security (Economics and region, 2024)
The paper identifies and substantiates the aspects of staffing and its potential in the security-oriented management of business processes in the course of restoring national economic security. The article offers a definition of security-oriented management of business processes as a model of realisation of tasks and functions performed within the framework of functioning of the economic system, which is aimed at satisfaction of needs and interests of their initiators with minimal risks of consumption of resources, obtaining untimely or incomplete achievement of the planned result as a result of completion of the operation. The publication outlines the directions for restoring national economic security, which require appropriate staffing to achieve the desired results in the future. It also identifies the vectors for forming and developing human resources to meet the needs of security-oriented management of business processes at domestic critical infrastructure enterprises.
Keywords: human resources; human resources potential; war; economic security; security-oriented management; critical infrastructure enterprise